Nurses' self‐esteem, self‐compassion and psychological resilience during COVID‐19 pandemic - George Vellaramcheril Joy; Albara Mohammad Ali Alomari; Kalpana Singh; Nesiya Hassan; Kamaruddeen Mannethodi; Jibin Kunjavara; Badriya Al Lenjawi (Wiley, 2023)
Abstract Aim This study aimed to identify self‐esteem, self‐compassion and psychological resilience among staff nurses during the COVID‐19 pandemic in Qatar. Design Descriptive cross‐sectional survey design. Methods The study was conducted on January 2022 (during the third wave in Qatar). Anonymous data were collected through an online survey using Microsoft forms from 300 nurses in 14 health facilities in Qatar. Socio‐demographic information, Connor‐Davidson Resilience Scale, Rosenberg Self‐Esteem Scale and Self‐Compassion Scale‐Short Form were used to collect the data. Correlation, t‐test and ANOVA analyses were conducted. Results Participants expressed a high level of resilience, self‐esteem and self‐compassion. Resilience scores were positively and significantly correlated with self‐esteem and self‐compassion. The education level of nurses was a statistically significant contributing factor to self‐esteem and resilience.